Delineation of seawater intrusion and groundwater quality assessment in coastal aquifers: The Korba coastal aquifer (Northeastern Tunisia). (March 2023) - Ayari, Jamel; Ouelhazi, Hassen; Charef, Abdelkarin; Barhoumi, Anis
Abstract: The aim of this study is to determine the general state of the Korba aquifer (northwestern Tunisia) with respect to seawater intrusion and to assess the suitability of groundwater for drinking and irrigation purposes. A total of 60 groundwater samples were collected and analysed for physicochemical parameters (pH, EC, TDS, Na +, K +, Ca 2+, Mg 2+, HCO3 −, Cl −, NO3 −, SO4 2− and Br − ). Major ionic ratios highlighted the dominance of the reverse ion exchange process triggered by the marine intrusion. Br − /Cl − ratio suggested that the irrigation with saline water and wastewater were potential additional sources of salinization. Hydrochemical Facies Evolution Diagram coupled with a GIS-based framework revealed that most of samples are located beneath the mixing line, showing dominant marine intrusion process. Based on the water quality index, most of groundwater samples were unsuitable for drinking. In addition, according to high sodium adsorption ratio, the groundwater quality was limited for irrigation purposes. Graphical abstract: Unlabelled Image Highlights: Geochemical approaches are used to identify the factors controlling groundwater mineralization in Korba coastal aquifer. Seawater intrusion, evaporation, anthropogenic activities and reverse cation exchange regulate groundwater chemistry. Seawater intrusion affects large proportion of coastal aquifer. Nitrate pollution is a consequence of anthropogenic activities.